2017
DOI: 10.1126/science.aag1772
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled ecomorphological evolution and diversification in Neogene-Quaternary horses

Abstract: Evolutionary theory has long proposed a connection between trait evolution and diversification rates. In this work, we used phylogenetic methods to evaluate the relationship of lineage-specific speciation rates and the mode of evolution of body size and tooth morphology in the Neogene and Quaternary radiation of horses (7 living and 131 extinct species). We show that diversification pulses are a recurrent feature of equid evolution but that these pulses are not correlated with rapid bursts in phenotypic evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 81 publications
3
81
1
2
Order By: Relevance
“…However, there is increasing empirical (Adams et al ; Cantalapiedra et al . ) and theoretical (Aristide & Morlon ) evidence that this coupling might not be so straightforward. Developing a model where both diversification and phenotypic evolution are influenced by competition for limited resources, Aristide & Morlon () found that niche packing limits speciation and increases extinctions rates, but does not reduce trait evolutionary rates, as frequent extinctions free up ecological space that is rapidly reoccupied.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing empirical (Adams et al ; Cantalapiedra et al . ) and theoretical (Aristide & Morlon ) evidence that this coupling might not be so straightforward. Developing a model where both diversification and phenotypic evolution are influenced by competition for limited resources, Aristide & Morlon () found that niche packing limits speciation and increases extinctions rates, but does not reduce trait evolutionary rates, as frequent extinctions free up ecological space that is rapidly reoccupied.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the overall dispersal along geological time‐scales was not constrained by past geographical distances; for example, when land bridges reconnected land masses that had remained isolated for millions of years and/or extinction events erased the signal of tectonic isolation. For instance, this is the case for the Great American Biotic Interchange (GABI) that recently brought new mammalian orders, such as cetartiodactyls and carnivorans, to South America (i.e., in the last 3–15 Ma; Bacon et al, ; Webb, ; Woodburne, ) or during the complex biogeographical history of horses (e.g., Cantalapiedra, Prado, Hernández Fernández, & Alberdi, ). As a result of these recent events, the β‐diversity of deep (e.g., at a time slice of 30 Ma in the current phylogeny) mammalian branches that we observe today between, for example, South and North America does not actually represent what the β‐diversity looked like 30 Ma between these continents.…”
Section: Discussionmentioning
confidence: 99%
“…with no motivating hypothesis related to alternative processes of range evolution presented by the candidate models. A few examples (of many) are Cantalapiedra, Prado, Hernández Fernández, and Alberdi (), Brown et al (), Givnish et al. (), Skeels and Cardillo () and Kok et al.…”
Section: Introductionmentioning
confidence: 99%